Issues of Physical Fitness of Young People in our Republic - Akhmadova Charos (Zien Journals, 2022)
This article highlights the important issues of ensuring a healthy lifestyle for young people, their spiritual, intellectual, physical and moral development, quality education, and effective use of health and sports infrastructure.
Keywords: healthy lifestyle; physical fitness; wellness; physical training